Factors influencing the willingness to implement and develop intelligent systems that can rely on artificial intelligence, machine learning, IoT or blockchain - Chaves, A.; Gonçalves, R.; Lopes da Costa, R.; Dias, Á.; Pereira, L. F. (International Journal of Business Performance Management, 2024)
Intelligent systems are one of today's greatest strengths. This study aims to understand what the major factors behind the possibility of developing and implementing these systems are. For that, an extensive literature review is conducted, mostly focused on concepts such as artificial intelligence (AI), the internet of things (IoT), or blockchain, among others. To understand how these technologies influence the possible implementation and faster roll-out of smart systems, a quantitative methodology was used, based on the application of an online survey, obtaining 100 valid answers worked through structural equations model (SEM). The obtained results show that factors such as the benefits of intelligent systems, the trust bestowed upon them, and the perception/knowledge about them have a positive and significant influence in developing and implementing intelligent systems. The conclusion that can be drawn is that there is an increased intention of using intelligent systems in management that comes from an increased knowledge and trust in their capabilities to deliver value to the business.